RELATIONSHIP BETWEEN QUALITY OF WORK LIFE AND NURSE’S PERFORMANCE IN EMERGENCY ROOM RSUD KARSA HUSADA BATU CITY - Dharma Pratiwi, Jiwani Alvina; Putri, Elsa Yosinda Widya Kusuma (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2025)
Quality of Work Life (QWL) is an important factor affecting nurse performance, especially in the Emergency Room (ER) with high work pressure. This study aims to analyze the relationship between QWL and the performance of ER nurses at RSUD Karsa Husada, Batu City. The research design used a quantitative method with a cross-sectional study approach. The total sampling used involved 17 ER nurses. QWL measurement was carried out through a structured questionnaire, while nurse performance was measured based on hospital performance evaluation indicators. The statistical test used was chi-square. The results showed a significant relationship between QWL and nurse performance with a p-value <0.005, which was 0.002 (α = 0.05). This indicates that improvements in QWL can contribute positively to improving nurse performance. These findings provide important implications for hospital management to improve the quality of the nurse work environment to achieve better performance in health services.